1993
DOI: 10.1111/j.1471-4159.1993.tb03202.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Chronic Nicotine Treatment on the Accumulation of [3H]Tetraphenylphosphonium by Cerebral Cortical Synaptosomes

Abstract: Chronic exposure of rats to nicotine increases the number of [3H]nicotine binding sites in the brain; however, it is not clear whether nicotinic cholinergic receptor function is altered as well. In this study, we have used [3H]tetraphenylphosphonium as a probe of synaptosomal membrane potential to investigate whether exposure to nicotine in vivo alters the ability of cerebral cortical synaptosomes to maintain a potential difference and to depolarize in response to in vitro nicotine. Treatment of rats for 14 da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

1993
1993
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…We found an extensive upregulation of [ 3 H]nicotine binding sites in the brain of nicotine‐treated rats, in agreement with many authors (Marks et al ., 1986; Romanelli et al ., 1988; Nordberg et al ., 1989; Collins et al ., 1990; Zhang et al ., 1994; Wall et al ., 2000). Only a few studies, however, reported the effect on [ 3 H]nicotine binding sites of constant infusion of nicotine, and at doses similar to those used in the present work (Morrow et al ., 1985; Fung & Lau, 1988; Hillard & Pounds, 1993; Sanderson et al ., 1993). Our data are consistent with those of Morrow et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We found an extensive upregulation of [ 3 H]nicotine binding sites in the brain of nicotine‐treated rats, in agreement with many authors (Marks et al ., 1986; Romanelli et al ., 1988; Nordberg et al ., 1989; Collins et al ., 1990; Zhang et al ., 1994; Wall et al ., 2000). Only a few studies, however, reported the effect on [ 3 H]nicotine binding sites of constant infusion of nicotine, and at doses similar to those used in the present work (Morrow et al ., 1985; Fung & Lau, 1988; Hillard & Pounds, 1993; Sanderson et al ., 1993). Our data are consistent with those of Morrow et al .…”
Section: Discussionmentioning
confidence: 99%
“…Only a few studies, however, reported the effect on [ 3 H]nicotine binding sites of constant infusion of nicotine, and at doses similar to those used in the present work (Morrow et al ., 1985; Fung & Lau, 1988; Hillard & Pounds, 1993; Sanderson et al ., 1993). Our data are consistent with those of Morrow et al . (1985), Hillard & Pounds (1993) and Sanderson et al .…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to the studies using periodic injections, the infusion of 1.5-4 mg/kg/day nicotine has resulted in less consistent increases in nAChR density, particularly in the striatum. Fung and Lau (1988), Drasdo and Wonnacott (1991), and Sanderson et al (1993) have reported little or no effect on striatal nAChR density from con-stant nicotine infusion, although others have found that nAChR density in the hippocampus and cortex appears to be increased by infusion of these doses (Morrow et al, 1985;Hillard and Pounds, 1993;Sanderson et al, 1993).…”
mentioning
confidence: 99%
“…Nevertheless, regular use of tobacco products creates chronic exposure to nicotine. Research from several laboratories demonstrates that chronic nicotine exposure creates a loss of nicotine-sensitive nAChR functional activity in the brain that can last for days in vivo (117), (118), (59), (60), (44), (42), (75), (76), (38). Through a process call “persistent inactivation,” the functions of nAChRs are lost due to chronic nicotine exposure in a time- and dose-dependent manner that is specific for each subtype.…”
Section: The Nicotinic Acetylcholine Receptor Nicotine and Its Imentioning
confidence: 99%
“…Many small trials have been conducted which demonstrate that subcutaneous and intravenous administration of nicotine has mild benefits in cognition in AD subjects, especially in areas of short-term memory, attention, and information processing (82), (90), (112), (48). Nicotine patches have also been found to have positive effects on attention in AD (107), (42), (105) (47). Large trials of ABT- 418, a nicotinic agonist have been undertaken (143).…”
Section: Smoking Ad and Cognitionmentioning
confidence: 99%